2018
DOI: 10.1161/circep.118.006604
|View full text |Cite
|
Sign up to set email alerts
|

Unifocal Right-Sided Ablation Treatment for Neurally Mediated Syncope and Functional Sinus Node Dysfunction Under Computed Tomographic Guidance

Abstract: Background Biatrial, extensive, and complex ablation strategies have been published for the treatment of neurally mediated syncope, sinus node dysfunction, and functional atrioventricular block. We have developed a less extensive and more specific approach compared with previously published cardioneuroablation strategies, called cardio-neuromodulation. It is based on tailored vagolysis of the sinoatrial node through partial ablation of the anterior right-ganglionated plexus, preferentially through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 14 publications
2
64
0
Order By: Relevance
“…Long-term efficacy of CNA in SND and AVB has been studied less than VVS (5,7,11,12) . In a recently published trial, Debruyne et al (12) studied the potential role of restricted right atrial approach in patients with SND and VVS and demonstrated a similar efficacy. However, short-term effects were presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term efficacy of CNA in SND and AVB has been studied less than VVS (5,7,11,12) . In a recently published trial, Debruyne et al (12) studied the potential role of restricted right atrial approach in patients with SND and VVS and demonstrated a similar efficacy. However, short-term effects were presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, we perform cardio‐neuromodulation (CardNM)—defined as a tailored vagolysis of the sinus node by targeting the ARGP plexus endocardially to prevent cardioinhibitory syncope and neurally mediated syncope (NMS) of the mixed type. Four years ago, we first targeted the ARGP from the left endocardium, and have moved to a right‐sided approach during the last 3 years . Our group also showed that the ARGP belongs to the final common pathway of sinus node vagal innervation in humans …”
mentioning
confidence: 99%
“…Four years ago, we first targeted the ARGP from the left endocardium, and have moved to a right‐sided approach during the last 3 years . Our group also showed that the ARGP belongs to the final common pathway of sinus node vagal innervation in humans …”
mentioning
confidence: 99%
See 2 more Smart Citations